Everyday Language Exposure Shapes Prediction of Specific Words in Listening Comprehension: A Visual World Eye-Tracking Study - Ito, Aine; Sakai, Hiromu (Frontiers in Psychology, 2021)
We investigated the effects of everyday language exposure on the prediction of orthographic and phonological forms of a highly predictable word during listening comprehension. Native Japanese speakers in Tokyo (Experiment 1) and Berlin (Experiment 2) listened to sentences that contained a predictable word and viewed four objects. The critical object represented the target word (e.g., <inline-graphic xlink:href="fpsyg-12-607474-i001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />/sakana/; fish), an orthographic competitor (e.g., <inline-graphic xlink:href="fpsyg-12-607474-i002.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />/tuno/; horn), a phonological competitor (e.g., <inline-graphic xlink:href="fpsyg-12-607474-i003.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />/sakura/; cherry blossom), or an unrelated word (e.g., <inline-graphic xlink:href="fpsyg-12-607474-i004.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />/hon/; book). The three other objects were distractors. The Tokyo group fixated the target and the orthographic competitor over the unrelated objects before the target word was mentioned, suggesting that they pre-activated the orthographic form of the target word. The Berlin group showed a weaker bias toward the target than the Tokyo group, and they showed a tendency to fixate the orthographic competitor only when the orthographic similarity was very high. Thus, prediction effects were weaker in the Berlin group than in the Tokyo group. We found no evidence for the prediction of phonological information. The obtained group differences support probabilistic models of prediction, which regard the built-up language experience as a basis of prediction.